1996
DOI: 10.1074/jbc.271.28.16703
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Structure of the N-terminal Splice Region of the Cyclic AMP-specific Phosphodiesterase RD1 (RNPDE4A1) by 1H NMR and Identification of the Membrane Association Domain Using Chimeric Constructs

Abstract: A 25-residue peptide representing the membrane targeting N-terminal splice region of the cyclic AMP phosphodiesterase RD1 (RNPDE4A1) was synthesized, and its structure was determined by 1 H NMR. Two independently folding helical regions were identified, separated by a highly mobile "hinge" region. The first helical region was formed by an N-terminal amphipathic ␣-helix, and the second consisted of multiple overlapping turns and contained a distinct compact, hydrophobic, tryptophan-rich domain (residues 14 -20)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 35 publications
3
55
0
Order By: Relevance
“…These results suggest that the molecular mechanism(s) of the membrane targeting of PDE4A1 and ApPDE4 long form mutants might be similar and through direct membrane association. The N terminus of PDE4A1 is involved in membrane association via two different motifs, namely, helix 1 and helix 2, that are separated by a hinge region (22,48). Our results showed that at least 16 N-terminal amino acids are required for sufficient membrane targeting of the long form.…”
Section: Discussionmentioning
confidence: 66%
“…These results suggest that the molecular mechanism(s) of the membrane targeting of PDE4A1 and ApPDE4 long form mutants might be similar and through direct membrane association. The N terminus of PDE4A1 is involved in membrane association via two different motifs, namely, helix 1 and helix 2, that are separated by a hinge region (22,48). Our results showed that at least 16 N-terminal amino acids are required for sufficient membrane targeting of the long form.…”
Section: Discussionmentioning
confidence: 66%
“…35 S]-labeled PDE4A1 for various binding studies (Smith et al, 1996;. Using a cDNA encoding fl-DISC1 as a template, we identified a single radiolabeled protein product of the expected size (100 kDa) in extracts analyzed on SDS-PAGE (data not shown).…”
Section: Probing Pde4d and Pde4b Peptide Arrays With Fl-disc1mentioning
confidence: 99%
“…The first of these helices (Helix-1; amino acids 1-8) comprises a Nterminal amphipathic ␣-helix whereas the second (Helix-2; amino acids 14-25) is a compact helical structure that is highly hydrophobic and tryptophan-rich (Smith et al, 1996). More recently we have identified a novel microdomain within helix-2, called TAPAS-1, which allows association with membranes and lipid vesicles .…”
Section: Introductionmentioning
confidence: 96%
“…analyses of the unique N-terminal region of PDE4A1 showed it to be composed of two distinct helical structures separated by a mobile 'hinge' region (Smith et al, 1996). The first of these helices (Helix-1; amino acids 1-8) comprises a Nterminal amphipathic ␣-helix whereas the second (Helix-2; amino acids 14-25) is a compact helical structure that is highly hydrophobic and tryptophan-rich (Smith et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation